Assessment of preload in carbon coated prosthetic screws - Dilcele Silva Moreira Dziedzic; Juliane Nhata; Vanessa Helena Jamcoski; Maurício Dziedzic (Revista Sul-Brasileira de Odontologia, 2013)
The mechanical aspects of tightening screws over implants are important to ensure a successful prosthetic rehabilitation. Screw loosening is a common problem that can be avoided with passive adaptation of the components and an increased tensile force developed in the screw, a preload. Objective: This in vitro study evaluated the effect on preload of a carbon lubricant deposited on the surface of titanium alloy prosthetic screws: conventional Ti6Al4V and surface enhanced. Material and methods: Conventional titanium alloy prosthetic (n = 7) and carbon coating surface enhanced screws (n = 7) were compared. Each prosthetic screw supporting a metallic UCLA over an implant was tightened with the manufacturer’s recommended torque of 32 N.cm. The removal torque values, recorded for ten consecutive cycles of tightening and removal, were used to estimate the preload. Implant blocks were then sectioned and the interfaces were observed by light microscopy. Results: The lowest removal torque, and consequently the highest preload values, was achieved for the lubricated group in most cycles. The contacts between threads were located at the coronal aspect of all observed screw mating threads. Conclusion: Data indicate that the lower coefficient of friction of a carbon lubricant can generate higher preload. The machining precision observed produced the adaptation and regular contact interfaces.